TGF-β activates APC through Cdh1 binding for Cks1 and Skp2 proteasomal destruction stabilizing p27kip1 for normal endometrial growth. Issue 7 (2nd April 2016) - Pavlides, Savvas C.; Lecanda, Jon; Daubriac, Julien; Pandya, Unnati M.; Gama, Patricia; Blank, Stephanie; Mittal, Khushbakhat; Shukla, Pratibha; Gold, Leslie I.
ABSTRACT: We previously reported that aberrant TGF-β/Smad2/3 signaling in endometrial cancer (ECA) leads to continuous ubiquitylation of p27 kip1 (p27) by the E3 ligase SCF-Skp2/Cks1 causing its degradation, as a putative mechanism involved in the pathogenesis of this cancer. In contrast, normal intact TGF-β signaling prevents degradation of nuclear p27 by SCF-Skp2/Cks1 thereby accumulating p27 to block Cdk2 for growth arrest. Here we show that in ECA cell lines and normal primary endometrial epithelial cells, TGF-β increases Cdh1 and its binding to APC/C to form the E3 ligase complex that ubiquitylates Cks1 and Skp2 prompting their proteasomal degradation and thus, leaving p27 intact. Knocking-down Cdh1 in ECA cell lines increased Skp2/Cks1 E3 ligase activity, completely diminished nuclear and cytoplasmic p27, and obviated TGF-β-mediated inhibition of proliferation. Protein synthesis was not required for TGF-β-induced increase in nuclear p27 and decrease in Cks1 and Skp2. Moreover, half-lives of Cks1 and Skp2 were extended in the Cdh1-depleted cells. These results suggest that the levels of p27, Skp2 and Cks1 are strongly or solely regulated by proteasomal degradation. Finally, an inverse relationship of low p27 and high Cks1 in the nucleus was shown in patients in normal proliferative endometrium and grade I-III ECAs whereas differentiated secretory endometrium showed the reverse. These studies implicate Cdh1 as the master regulator of TGF-β-induced preservation of p27 tumor suppressor activity. Thus, Cdh1 is a potential therapeutic target for ECA and other human cancers showing an inverse relationship between Cks1/Skp2 and p27 and/or dysregulated TGF-β signaling.